Teaching children to write and read in Waldorf schools - Bell, Amanda (Frontiers in Education, 2024)
A well-established principle of Waldorf Education is that children’s development is compromised if we bring intellectual teaching too early. Waldorf teachers congratulate themselves that they wait until the seventh year to begin formal schooling, but according to the principles of child development out of which Waldorf Education arose, and on which much of our practice has been based for a hundred years, teaching children to read and write at seven is not ideal; they are still not ready. Convention and state expectations made it necessary in 1919, just as they do now, to introduce literacy teaching at an age not too far from what was generally considered normal, so a compromise was needed. Steiner suggested that, because physical development reaches a certain completion at seven, it is less harmful if we can wait until then. But according to Steiner, this is still a compromise: we cannot immediately unleash any kind of teaching scheme on children as soon as they reach their seventh year without doing any harm. According to modern teaching principles and methods, starting earlier means getting ahead; everything should be taught explicitly and systematically; and nothing can be left to develop of its own accord. Proponents of synthetic phonics refer to impressive research showing that it produces better results than other methods of teaching literacy, which is why it has been adopted so widely in mainstream education. However, the validity of this claim depends on what we mean by ‘better results’ and ‘literacy’. This paper explores these ideas.